Human papillomavirus 16 detected in nasopharyngeal carcinomas in white Americans but not in endemic Southern Chinese patients. Issue 5 (26th October 2013) - Lin, Zhixiong; Khong, Brian; Kwok, Shirley; Cao, Hongbin; West, Robert B.; Le, Quynh‐Thu; Kong, Christina S.
Abstract Background We evaluated the relationship of human papillomavirus (HPV) and Epstein–Barr virus (EBV) with race in endemic and nonendemic cohorts of patients with nasopharyngeal carcinoma (NPC), and with smoking status in the nonendemic cohort. Methods Tissue microarrays (TMAs) were constructed using samples from 86 patients treated in southern China and 108 patients from Stanford, California. TMAs were stained with p16, HPV in situ hybridization (ISH), and EBV ISH. Polymerase chain reaction (PCR) was used to confirm EBV(‐) cases and HPV status in p16(+) cases. Survival data was available for the Stanford cohort only. Results No HPV(+) cases were detected in the Chinese cohort. In the Stanford cohort, 5 of 11 EBV(‐) cases harbored HPV‐16, 10 of 10 occurred in whites, and 8 of 11 were smokers. Patients with EBV(‐) NPC also showed a trend toward worse survival. Conclusion EBV(‐) NPC shows an association with the presence of HPV, white race, and smoking. In contrast, EBV(‐) NPC shows no association with HPV in the endemic cohort. © 2013 Wiley Periodicals, Inc. Head Neck36: 709–714, 2014